Intraoperative Endoscopic-Guided Bowel Resection for Persistent Gastrointestinal Bleeding Caused by Angiodysplasia: A Case Report and Literature Review - Fellows, Emily; Harris, Joy; Kibble, Tania; McDonald, Nicholas M.; Azeem, Nabeel; Harmon, James V. (The Surgery Journal, 2023)
Gastrointestinal angiodysplasia is an uncommon condition often associated with significant gastrointestinal bleeding that is resistant to medical therapy. We report the clinical outcomes of two patients who successfully underwent simultaneous intraoperative endoscopic and surgical interventions for the treatment of angiodysplasia. Intraoperative endoscopic guidance was found to be useful in managing hemorrhage caused by angiodysplasia in both patients. Additionally, we performed an analysis of cases reported in the literature. Our review focused on the anatomic location of the resected bowel and the clinical outcomes of patients (n = 21) with angiodysplasia managed with intraoperative endoscopy reported in the literature.
Keywords: angiodysplasia; intraoperative endoscopy; bowel resection; gastrointestinal hemorrhage